Sampling Plants and Malacofauna in 87Sr/86Sr Bioavailability Studies: Implications for Isoscape Mapping and Reconstructing of Past Mobility Patterns - Britton, Kate; Le Corre, Mael; Willmes, Malte; Moffat, Ian; Grün, Rainer; Mannino, Marcello A.; Woodward, Stephen; Jaouen, Klervia (Frontiers in Ecology and Evolution, 2020)
Establishing strontium isotope (87Sr/86Sr) geographical variability is a key component of any study that seeks to utilize strontium isotopes as tracers of provenance or mobility. Although lithological maps can provide a guideline, estimations of bioavailable 87Sr/86Sr are often necessary, both in qualitative estimates of local strontium isotope ‘catchments’ and for informing/refining isoscape models. Local soils, plants and/or animal remains are commonly included in bioavailability studies, although consensus on what (and how extensively) to sample is lacking. In this study, 96 biological samples (plants and snails) were collected at 17 locations spanning 6 lithological units, within a region of south-west France and area with a high concentration of Palaeolithic archaeological sites. Sampling sites aligned with those from a previous study on soil bioavailable strontium, and comparison with these values, and the influence of environmental and anthropogenic variables, was explored. Data confirm a broad correspondence of plant and snail 87Sr/86Sr values with lithological unit/soil values, although the correlation between expected 87Sr/86Sr values from lithology and bioavailable 87Sr/86Sr ratios from biological samples was higher for plants than for snails. Grass, shrub and tree 87Sr/86Sr values were similar but grasses had a stronger relationship with topsoil values than trees, reflecting differences in root architecture. Variability in 87Sr/86Sr ratios from all plant samples was lower for sites located on homogeneous geological substrates than for those on heterogeneous substrates, such as granite. Among environmental and anthropogenic variables, only an effect of proximity to water was detected, with increased 87Sr/86Sr values in plants from sites close to rivers originating from radiogenic bedrock. The results highlight the importance of analysing biological samples to complement, inform and refine strontium isoscape models. The sampling of plants rather than snails is recommended, including plants of varying root depth, and (if sample size is a limitation) to collect a greater number of samples from areas with heterogeneous geological substrates to improve the characterizations of those regions. Finally, we call for new experimental studies on the mineralized tissues of grazers, browsers, frugivores and/or tree leaf feeders to explore the influence of 87Sr/86Sr variability with soil profile/root architecture on 87Sr/86Sr values of locally-feeding fauna.